Associated Religious/Spiritual Coping Factors Among Children with Chronic Health Conditions - da Silva Ferreira, Giovanna (2024)
Introduction: Children who experience chronic illnesses use their spirituality to cope with and adapt to the situation and health condition, therefore care focused on the spiritual dimension and its associated factors promotes a comprehensive approach in this context. Objective: To identify the factors associated with religious/spiritual coping among children with chronic health conditions. Methods: Cross-sectional, analytical, and correlational study involving children with chronic health conditions monitored in the outpatient service of a university hospital. Data was collected from August 2021 to January 2023 through interviews using the Characterization Instrument and Religious Coping Scale for Children. Data analysis used descriptive statistics and association research using non-parametric measures: Spearman correlation coefficient, Kruskal Wallis Test, and Mann Whitney Test. Results: Thirty-four children participated, with a median age of 10 years, the majority were male, white, had siblings, lived with their parents, and believed in God. Positive religious coping strategies predominated, with strategies focused on the belief in God's support. Individual, religious, and clinical characteristics shown to influence children's religious/spiritual coping were skin color, education, siblings, beliefs in God, religion, and the affected system by the health condition. Conclusion: Children with chronic health conditions engage in positive religious coping strategies, which are influenced by their individual, religious, and clinical characteristics, and, therefore, this is an aspect that should receive attention from health professionals.